A low-cost current flow controlling interline hybrid circuit breaker combined with SCR and H-bridge sub-module - Zeng, Qingpeng; Zhu, Jin; Guo, Xinming; Huo, Qunhai; Yin, Jingyuan; Wei, Tongzhen (Frontiers in Energy Research, 2023)
A massive number of DC circuit breaker is usually necessary to be installed to protect HVDC grids from DC faults, this will lead to high capital costs because large number of expensive IGBT-in-series are used. In this paper, an interline hybrid circuit breaker is proposed by the combination of SCR string and a small number of H-bridge modules (SCR-IHCB). The proposed SCR-IHCB has the capacity of blocking DC fault of two adjacent lines respectively by sharing only one main breaker branch (MB) mainly composed of low-cost SCR string and H-bridge module instead of IGBT-in-series string. The interline current flow control function is also integrated. Hence it has advantages of simple and compact topology, economical design compared with typical IGBT based HCB solutions. The operation process of the proposed SCR-IHCB is discussed in detail, and the performance is veriﬁed by MATLAB Simulink simulation and scale-down prototype experiment.